Leadership Agility in Realizing Adaptive and Precise Polri in the Vuca Era - Nasri Nasri; Nopta Histaris Suzan; Amril Muhammad (Journal of Social Research, 2023)
After Covid 19, the condition of society globally has shifted towards an era better known as VUCA or the era of uncertainty. In this situation, the leader of a group or organization – in this case the police – who faces various risks must find a solution to the problem by changing the leadership model. Agility is considered to be able to overcome the conditions of ambiguity caused by the uncertainty of the fast-paced disruption era without clear direction of destination. This research is a qualitative study using secondary data sources in the form of information from articles and mass media. The results of the study concluded that agile leadership can be a solution so that the National Police can be adaptive and precise in the VUCA era. An agile leader is considered capable of navigating organizational performance capabilities that are faster, adaptive, superior, and productive.